Sex difference in aortic valve fibrosis assessed by contrast-enhanced computed tomography in severe aortic stenosis. (14th October 2021) - Myasoedova, V; Fraschini, E; Mostardini, G; Bonfanti, L; Chiesa, M; De Pasquale, C; Olivares, P; Trabattoni, D; Bartorelli, A L; Andreini, D; Poggio, P
Abstract: Background: Aortic stenosis (AS) is characterized by fibro-calcific remodeling of aortic valve leaflets. Progressive aortic valve calcification (AVC) occurs in both sexes and cardiac computed tomography (CT) is recognized as a high-quality technique for AVC evaluation. To date, sex-specific CT thresholds of AVC have been implemented in clinical practice since it is now recognized that women have less AVC burden than men. In addition, recent evidences indicate that women have more fibrotic remodeling of aortic valve leaflet compared to men. Purpose: Aortic valve fibrosis (AVF) being a significant contributor to valve gradient, we sought to evaluate the difference in AVF burden between men and women with severe AS using contrast-enhanced CT. Methods: We included 56 patients matched for age and sex with severe AS. All patients underwent Doppler echocardiography and cardiac CT before intervention. Contrast attenuation values (Hounsfield Units, HU) and contrast-to-noise ratio were measured at the level of the ascending aorta. Total AVF was assessed based on HU ranging between 30 and 350, adjusting the upper threshold by increments of 25 HU in either direction until blood pool was not highlighted. Indexed contrast-enhanced CT calcium volume (iAVC) and fibrosis volume (iAVF) were calculated dividing the volumes by the aortic annular area. Fibro-calcific ratio was calculate dividing iAVF by iAVC volumes. Results: There was no difference between men and women in major cardiovascular risk factors, valve phenotype (bicuspid vs. tricuspid), nor pharmacological treatment. Men had higher body surface area than women (1.89±0.14 vs. 1.67±0.17 m 2, respectively; p<0.001), while women had lower aortic valve area than men (AVA; 0.74±0.2 vs. 0.91±0.2 cm 2, respectively; p=0.007) but similar indexed AVA (0.44±0.15 vs. 0.48±0.12 cm 2 /m 2, respectively; p=0.262). Women had significantly lower iAVC compared to men (36 [36–72] vs. 72 [67–123] mm 3 /cm 2, respectively; p=0.03). However, iAVF was significantly higher in women compared to men (83 [78–123] vs. 63 [58–83] mm 3 /cm 2, respectively; p=0.006). Finally, the fibro-calcific ratio, which indicates the predominance of valve fibrosis if >1.0, was significantly higher in women compared to men (2.57 [2.14–7.02] vs. 0.78 [0.84–2.02], respectively; p=0.003). Conclusions: Our study highlights for the first time a sex difference in the fibrotic content of severe AS evaluated by contrast-enhanced CT. These findings might be valuable to promote further studies on the role of sex-specific tissue composition in AS progression and outcomes. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Fondazione Gigi e Pupa Ferrari ONLUS